Sulfidation of electrodeposited microcrystalline/nanocrystalline cuprous oxide thin films for solar energy applications - Jayathilaka, K.M.D.C.; Siripala, W.; Kapaklis, V.; Jayanetti, J. K. D. S. (My University, 2012)
Grain size of polycrystalline semiconductor thin films in solar cells is optimized to enhance the efficiency of solar cells. This paper reports results on an investigation carried out on electrodeposited n-type cuprous oxide (Cu2O) thin films on Ti substrates with small crystallites and sulfidation of them to produce a thin-film solar cell. During electrodeposition of Cu2O films, pH of an aqueous acetate bath was optimized to obtain films of grain size of about 100 nm, that were then used as templates to grow thicker n-type nanocrystalline Cu2O films. XRD and SEM analysis revealed that the films were of single phase and the substrates were well covered by the films. A junction of Cu2O/CuxS was formed by partially sulfiding the Cu2O films using an aqueous sodium sulfide solution. It was observed that the photovoltaic properties of nano Cu2O/CuxS heterojunction structures are better than micro Cu2O/CuxS heterojunction solar cells. Resulting Ti/nano Cu2O/CuxS/Au solar cell structure produced an energy conversion efficiency of 0.54%, Voc = 610 mV and Jsc = 3.4 mA cm−2 , under AM 1.5 illumination. This is a significant improvement compared to the use of microcrystalline thin film Cu2O in the solar cell structure where the efficiency of the cell was limited to 0.11%. This improvement is attributed mainly to the increased film surface area associated with nanocrystalline Cu2O films.
Keywords: Cuprous oxide; Aqueous acetate bath; Electrodeposition; Photovoltaic properties; Polycrystalline semiconductor